System of Quality monitoring for IP Telephony Services. - Vetter, Murilo; Willrich, Roberto (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2014)
IP telephony is a consolidated service that has been growing steadily, driven by its various advantages. However, maintaining the quality of this service is still a challenge. As the telephony is an essential service for various organizations, the IP telephony must maintain reasonable call qualities. Therefore, the quality offered by the IP telephony service must be constantly monitored to guide maintenance actions. This paper proposes an end-to-end quality monitoring system for IP telephony services based on the reporting package RTCP-XR and using the SIP signaling protocol. A use case of the proposed system on an IP telephony production service of a university shows its effectiveness and versatility.